Actividades lúdicas como fomento al valor de la equidad de género - Valenzuela Bustamante, Mercedes Piedad (2021)
This case study aims to investigate the particularities and factors that may tend to promote equity in basic education students, starting from the aforementioned aspects. The game is a component that allows generating spaces for reflection, the gender perspective seeks respect to achieve a harmonious level of coexistence, recreational activities to promote gender equality, aims to strengthen the global and integral development of children and 5th grade girls, for the development of this analysis the inductive method was used, obtaining principles, strategies and values in the educational institution, the same ones that help to improve the teaching-learning of the student. Since this allows the development of an equitable, balanced society where human rights predominate as equals, since students are there, where they begin to give more relevance to their social environment, thus welcoming an identity that in the future will strengthen their own personality. , in turn, they can raise awareness, take a position on controversial issues and develop in an egalitarian environment. Since current education is based on the psychological evolution of the different activities of children's games, including the playful aspect as part of comprehensive training, facilitating the free acquisition of knowledge that allows children to choose opportunities and factors that spontaneously produces and promotes the enjoyment of a better standard of living in their daily lives. For this reason, this research seeks to establish the importance and influence that recreational activities have on the topic addressed and on the teaching of gender equity.